Struktur Naratif Cerpen â€œAl-Imraâ€™at Ghalabati As-Syaitonâ€ Karya Taufiq El-Hakim (Kajian Naratologi A.J.Greimas) - Fatimah, Nisa; Supriadi, Dedi; Komarudin, Edi (Hijai - Journal on Arabic Language and Literature, 2018)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  The aim in this study is 1) to learn scheme aktan contained in the short stories of women that trick the Devils work Taufiq el-Hakim, and 2) to find out the relationship between structure and functional structure aktan in the formation of structure the story. As for the method used in this research is descriptive method with the data gathering techniques in the form of the technique note and the study of librarianship. The source of the data in this study is the short story of the woman who deceived the Devils, and the data in this study is the word or phrase contained in the short stories of women that trick the Devils. Based on research conducted there is one schema aktan and functional model structure that exists in the text or sentence short women the Devils work beguiling Taufiq el-Hakim. The relationship between structure and functional structure aktan, there is one pattern that becomes aktan scheme structures the story namely aktan scheme contained in the short stories of women that trick the Devils work Taufiq el-Hakim. This gives rise to the existence of a aktansial scheme of events that become the structure of the story of the woman who deceived the Devils.Â Keywords: short stories of women that trick the Devils, aktan scheme, a functional structure, naratologi A.J. Greimas.Â Ù…Ù„Ø®Øµ Ø§Ù„Ø¨ØØ«Â ÙˆØ§Ù„Ø£ØºØ±Ø§Ø¶ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ 1) Ù„Ù…Ø¹Ø±ÙØ© Ù…Ø®Ø·Ø· Ø§Ù„Ø£ÙƒØªØ§Ù† ÙÙŠ Ù‚ØµØ© Ø§Ù„Ù‚ØµÙŠØ±Ø© Ø¥Ù…Ø±Ø£Ø© ØºÙ„Ø¨Øª Ø§Ù„Ø´ÙŠØ·Ø§Ù† Ù„ØªÙˆÙÙŠÙ‚ Ø§Ù„ØÙƒÙŠÙ….Â  2) Ù„Ù…Ø¹Ø±ÙØ© Ø§Ù„Ø¹Ù„Ø§Ù‚Ø© Ø¨ÙŠÙ† Ø¨Ù†ÙŠØ© Ø£ÙƒØªØ§Ù† Ùˆ Ù‡ÙŠÙƒÙ„ ÙˆØ¸ÙŠÙØªÙ‡ ÙÙŠ ØªØ´ÙƒÙŠÙ„ Ø¨Ù†ÙŠØ© Ø§Ù„Ù‚ØµØ©. Ø§Ø³ØªØ®Ø¯Ù… Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù…Ù†Ù‡Ø¬Ø§ ÙˆØµÙÙŠØ§ Ùˆ ÙˆÙŠØ³ØªØ®Ø¯Ù… Ù…Ù†Ù‡Ø¬ Ø§Ù„Ù…Ù„Ø§ØØ¸Ø© ÙˆØ§Ù„ØªØ³Ø¬ÙŠÙ„ simak catat Ùˆ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ù…ÙƒØªØ¨ÙŠØ© ÙˆØ£Ù…Ø§ Ù…ØµØ¯Ø± Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙÙŠ Ù‡Ø° Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ù‚ØµØ© Ù‚ØµÙŠØ±Ø© "Ø§Ù„Ø§Ù…Ø±Ø£Ø© ØºÙ„Ø¨Øª Ø§Ù„Ø´ÙŠØ·Ø§Ù† Ù„Ù„ØªÙˆÙÙŠÙ‚ Ø§Ù„ØÙƒÙŠÙ… ÙˆØ§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙÙŠÙ‡ Ù‡ÙŠÂ  Ø§Ù„ÙƒÙ„Ù…Ø§Øª ÙÙŠ Ù‚ØµØ© Ù‚ØµÙŠØ±Ø© "Ø§Ù„Ø§Ù…Ø±Ø£Ø© ØºÙ„Ø¨Øª Ø§Ù„Ø´ÙŠØ·Ø§Ù† Ù„Ù„ØªÙˆÙÙŠÙ‚ Ø§Ù„ØÙƒÙŠÙ…". Ø§Ø³ØªÙ†ØªØ¬Øª Ø§Ù„Ø¨Ø§ØØ«Ø© Ø§Ù† Ù…Ø®Ø·Ø· Ø§Ù„Ø£ÙƒØªØ§Ù† ÙˆØªØ±ÙƒÙŠØ¨ ÙˆØ¸ÙŠÙÙŠ ÙÙŠ Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ù‚ØµØ© Ù‚ØµÙŠØ±Ø© "Ø§Ù„Ø§Ù…Ø±Ø£Ø© ØºÙ„Ø¨Øª Ø§Ù„Ø´ÙŠØ·Ø§Ù† Ù„Ù„ØªÙˆÙÙŠÙ‚ Ø§Ù„ØÙƒÙŠÙ…". ÙˆØªÙˆØ¬Ø¯ Ø§Ù„Ø¨Ø§ØØ«Ø© Ù†Ù…Ø· Ù…Ø®Ø·Ø· Ø§Ù„Ø£ÙƒØªØ§Ù† ÙÙŠ Ø§Ù„Ø¹Ù„Ø§Ù‚Ø© Ø¨ÙŠÙ† Ù‡ÙŠÙƒÙ„ Ø§Ù„Ø£ÙƒØªØ§Ù† ÙˆØ§Ù„Ù‡ÙŠÙƒÙ„ Ø§Ù„ÙˆØ¸ÙŠÙÙŠÂ  ÙˆØ£Ù…Ø§ ØªØ±ÙƒÙŠØ¨ Ø§Ù„Ù‚ØµØ© Ù‡Ùˆ Ù…Ø®Ø·Ø· Ø§Ù„Ø£ÙƒØªØ§Ù† ÙÙŠ Ù‚ØµØ© Ù‚ØµÙŠØ±Ø© "Ø§Ù„Ø§Ù…Ø±Ø£Ø© ØºÙ„Ø¨Øª Ø§Ù„Ø´ÙŠØ·Ø§Ù† Ù„Ù„ØªÙˆÙÙŠÙ‚ Ø§Ù„ØÙƒÙŠÙ…" ÙŠØ³Ø¨Ø¨ Ù…Ø®Ø·Ø· Aktansial Ø¹Ù„Ù‰ ÙˆØ¬ÙˆØ¯ Ø§Ù„Ù…Ù†Ø§Ø³Ø¨Ø§Øª Ø§Ù„Ø®Ø§ØµØ© ÙÙŠ ØªØ±ÙƒÙŠØ¨ Ø§Ù„Ù‚ØµØ© "Ø§Ù…Ø±Ø£Ø© ØºÙ„Ø¨Øª Ø§Ù„Ø´ÙŠØ·Ø§Ù† Ù„Ù„ØªÙˆÙÙŠÙ‚ Ø§Ù„ØÙƒÙŠÙ….Â ÙƒÙ„Ù…Ø§Øª Ù…ÙØªØ§ØÙŠØ© : Ù‚ØµÙŠØ±Ø© Ù‚ØµÙŠØ±Ø© " Ø¥Ù…Ø±Ø§Ø© ØºÙ„Ø¨Øª Ø§Ù„Ø´ÙŠØ·Ø§Ù†"ØŒ Ù…Ø®Ø·Ø· Ø§Ù„Ø£ÙƒØªØ§Ù†ØŒ Ø§Ù„ØªØ±ÙƒÙŠØ¨ Ø§Ù„ÙˆØ¸ÙŠÙÙŠØŒ Ø§Ù„Ù†ÙˆØ±ÙˆØªÙˆÙ„ÙˆØ¬ÙŠ Ù„Ø£Ø¬ ØºØ±ÙŠÙ…Ø§Ø³.Â ABSTRAKÂ Tujuan dalam penelitian ini adalah 1) untuk mengetahui skema aktan yang terdapat dalam cerpen Al-Imraâ€™at Ghalabati As-Syaiton karya Taufiq el-Hakim, dan 2) untuk mengetahui hubungan antara struktur aktan dan struktur fungsional dalam pembentukan struktur cerita. Adapun metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan teknik pengumpulan datanya berupa teknik catat dan studi kepustakaan. Sumber data dalam penelitian ini adalah cerpen Al-Imraâ€™at Ghalabati As-Syaiton, dan data dalam penelitian ini adalah kata atau kalimat yang terdapat dalam cerpen Al-Imraâ€™at Ghalabati As-Syaiton. Berdasarkan penelitian yang dilakukan terdapat satu skema aktan dan struktur model fungsional yang ada dalam teks atau kalimat cerpen Al-Imraâ€™at Ghalabati As-Syaiton karya Taufiq el-Hakim. Hubungan antara struktur aktan dan struktur fungsional terdapat satu pola skema aktan yang menjadi struktur cerita yaitu skema aktan yang terdapat dalam cerpen Al-Imraâ€™at Ghalabati As-Syaiton karya Taufiq el-Hakim. Skema aktansial ini menimbulkan adanya peristiwa-peristiwa yang menjadi struktur cerita Al-Imraâ€™at Ghalabati As-Syaiton.Â Kata kunci: cerpen Al-Imraâ€™at Ghalabati As-Syaiton, skema aktan, struktur fungsional, naratologi A.J. Greimas.